Advanced seismic imaging techniques characterize the Alpine Fault at Whataroa (New Zealand). Issue 12 (16th December 2016) - Lay, V.; Buske, S.; Lukács, A.; Gorman, A. R.; Bannister, S.; Schmitt, D. R.
Abstract: The plate‐bounding Alpine Fault in New Zealand is an 850 km long transpressive continental fault zone that is late in its earthquake cycle. We have acquired and processed reflection seismic data to image the subsurface around the main drill site of the Deep Fault Drilling Project (DFDP‐2). The resulting velocity models and seismic images of the upper 5 km show complex subsurface structures around the Alpine Fault zone. The most prominent feature is a strong reflector at depths of 1.5–2.2 km with an apparent dip of 48° to the southeast below the DFDP‐2 borehole, which we assume to be the main trace of the Alpine Fault. Above the main reflector, parallel reflectors suggest the presence of a ∼600 m wide damage zone. Additionally, subparallel reflectors are imaged that we interpret as secondary branches of the main fault zone. Conjugate faults imaged by the data show the complexity of the subsurface. The derived P wave velocity model reveals a 300–600 m thick sedimentary layer with velocities of ∼2.3 km/s above a schist basement with velocities of 4.5–5.5 km/s. A low‐velocity layer can be observed within the basement at 0.8–2 km depth. A small‐scale low‐velocity anomaly appears at the top of the basement that can be correlated to the fault zone. The results provide a reliable basis for a seismic characterization of the DFDP‐2 drill site that can be used for further structural and geological investigations of the architecture of the Alpine Fault in this area. Key Points: Seismic reflections of the Alpine Fault imaged around the DFDP‐2 drill site P wave velocity models show a complex subsurface structure Main Alpine Fault reflector dips ∼48° SE and has subparallel fault branches